(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Denis I. Petrenko, Klara E. Shtein (Stavropol`, Russian Federation) The paper is devoted to the rare genre of «memoir of a map» widespread in Great Britain in the 18th century. The authors analyze the little-known George Ellis’s book «Memoir of a Map of the Countries Comprehended Between the Black Sea and the Caspian; with an Account of the Caucasian Nations, and Vocabularies of Their Languages» which precedes researches on comparative-historical linguistics and linguistic geography. George Ellis’s book is especially interesting to those who learn languages, history and culture of the Caucasian people. The book contains «specimen of Caucasian languages» representing a basic lexical fund (lexical kernel) of seven Caucasian languages and their dialects: Abkhazian, Circassian, Ossetian, Ingush, Lezghin, Georgian. The book is introduced in scientific use in the field of comparative-historical linguistics and Caucasus studies for the first time. Key words: memoir of a map, linguistic research of culture, linguistic research of geography. DOI 10.23683/1995-0640-2017-3-113-120